Reconstructing Political Finance Regulation in Indonesia’s Multiparty Democracy - Firmansyah Putra; Dimas Subekti; Dinda Syufradian Putra; Ansorullah Ansorullah; Mochammad Farisi (Universitas Lampung, 2026)
This study examines how Indonesia's political party finance regulations can be redesigned to strengthen transparency and accountability in a multiparty system. Using normative legal research based on statutory and legal theory approaches, it finds that the current framework remains ineffective because of limited public disclosure, weak independent auditing, fragmented oversight, and inadequate regulation of political contributions. The study proposes an integrated governance model comprising six regulatory pillars: standardized public financial reporting, a national digital reporting system, independent audits by the State Audit Agency (BPK), stricter regulation of private donations, performance-based public funding, and institutionalized public oversight. The study contributes to the political finance literature by advancing an integrated governance model for political party finance in multiparty democracies.